Money as a contingency factor: an approach under various theories (Revista Científica Compendium, 2024)
This essay presents a reflection on the absolute and relative impact of money as a motivational factor at work, leaving aside the apparent superficiality with which it has been treated as just another element in the respective process. It is estimated that not only does it maintain a priority weight as a motivational element, but under certain circumstances it can be instrumentalized as a “wild card or nutrient” for the satisfaction of another body of non-financial needs, as long as it is perceived that way by the person and/or the organization makes it known. Likewise, it is clear the existence of exceptions or exceptional scenarios that generate some gaps at the level of work to relativize its effect, without necessarily losing in some way its referent value in the activation and maintenance of behavior. For the analysis and respective reflections, use was made of specific theories on the topic, bibliographic reviews, unstructured interviews and support from the author's academic and work experience, which, complemented with other general theoretical approaches, seek to explain the scope of money in the organizational framework, without detriment to any other factors binding to the respective topic.
Keywords: contingency; money; incentives; motivation; theories